Nalbuphine and dexmedetomidine as adjuvants to ropivacaine in ultrasound-guided erector spinae plane block for video-assisted thoracoscopic lobectomy surgery: A randomized, double-blind, placebo-controlled trial. Issue 32 (13th August 2021) - Rao, Jin; Gao, Zhixin; Qiu, Gaolin; Gao, Pei; Wang, Qing; Zhong, Weiwei; Wang, Yiqiao; Li, Yuanhai
Abstract: Background: Adjuvants to local anesthetics, such as nalbuphine and dexmedetomidine, can be used to improve the quality and duration of peripheral nerve block effects. Dexmedetomidine has been successfully used as an adjuvant of erector spinae plane block (ESPB) with ropivacaine in video-assisted thoracoscopic lobectomy surgeries (VATLS). This study aimed to compare the effects of nalbuphine and dexmedetomidine used as adjuvants to ropivacaine for ESPB in VATLS. Methods: A total of 102 patients undergoing VATLS with ESPB were enrolled and randomized into 3 groups, each of which received a different adjuvant to ropivacaine. The visual analogue scale score, onset and duration of sensory block, use of patient-controlled analgesia (PCA), rate of rescue analgesia, duration of postoperative hospitalization, incidence of postoperative nausea and vomiting, and chronic pain were measured and observed. Results: The visual analogue scale score, total PCA use, rate of rescue analgesia, and postoperative chronic pain in the ropivacaine with dexmedetomidine (RD), and ropivacaine with nalbuphine (RN) groups were lower than those in the ropivacaine (RC) group ( P  < .05). The duration of sensory block was longer and the first use of PCA occurred later in the RD and RN groups than they did in the RC group ( P  < .05). Conclusions: As an adjuvant to ropivacaine in ESPB, nalbuphine and dexmedetomidine are comparable in terms of the associated analgesia, sensory block duration, need for rescue analgesia, and incidence of chronic pain in patients after VATLS.